Analisis Kesulitan Belajar Bahasa Arab Siswi Kelas 1 Kmi A Semester Genap Pondok Pesantren Al-Mujtama’ Al Islami - Herta Lapiana; Rima Ajeng Rahmawati; M. Wisnu Khumaidi (Program Studi Pendidikan Bahasa Arab, 2022)
This research is based on the dificculties of learningArabic students have in the learning process at theIslamic boarding school. As for the background inthis study, the first grade students of KMI A Islamicboarding school AL-Mujtama’ Al Islami ati AgungLampung south have not met the target and feeldifficulty and difficulty understanding it becausefor them Arabic is a foreign language. What isgeneral formulation and purpose of learning Arabicin the AL-Mutama Al Islamic boarding school is tofind out the difficulaty factors experienced bystudents in learning Arabic in the AL-Mujtama’ AlIslamic boarding school. This study used aqualitative descriptive research method. The subejctof this study was a first – class student at the ALMujtama’ Al Islamic boarding school. This isresearch was conducted in the even seester on thesixth of April to thirteenth of the acadeic year oftwo thousand nineteen two thousand and twenty.The results showed that first, there was a lack ofotivation from students in the sorroundingenvironment to learn Arabic. Second the teacher’sdelivery is too monotonous who only uses thelecture method and the use of learning media onlyuses books so that students feel uninterested inlearning Arabic ore deeply.